Physicochemical Characterization and Chemical Profiling of Essential Oils from Mountainous Zingiber Species in Vietnam - Nguyen Thi, Minh Tu THI MINH; My Chau, Le Thi; Thang, Tran Dinh; Thao, Nguyen Thi; Ngoc Thu, Tran Thi; Le Hang, Hoang Thi (Universitas Jenderal Soedirman, 2026)
ABSTRACT: This study aims to characterize and compare the physicochemical properties and chemical composition of essential oils derived from seven indigenous Zingiber species collected from mountainous regions of Vietnam, with the goal of supporting species differentiation and quality assessment. Essential oils were evaluated through integrated physicochemical characterization and chemical profiling. Key quality indicators, including optical rotation, refractive index, density, acid value, and ethanol solubility, were determined according to national standards. Chemical composition was analyzed using gas chromatography–mass spectrometry (GC–MS). Gas chromatography-mass spectrometry (GC-MS) analysis identified a total of 80 volatile compounds across all samples, with monoterpene hydrocarbons, oxygenated monoterpenes, and sesquiterpene hydrocarbons as the predominant classes. Major constituents varied markedly among species, with citronellal (up to 30%), β-pinene (>20%), γ-terpinene and 1,8-cineole (collectively up to 30%), and α-pinene (>50% in some species) representing the dominant compounds. Significant variation in both physical and chemical parameters among species enabled effective discrimination and revealed distinct chemical markers such as β-pinene, γ-terpinene, zingiberene, citronellal, and nootkatone. The results provide species-specific chemical fingerprints useful for differentiation and quality assessment of Zingiber essential oils. Although pathway-based clustering analysis was beyond the scope of this study, the findings contribute to the development of traceability frameworks and support the valorization of Vietnamese mountainous ginger resources in pharmaceutical, food, and cosmetic applications. Keywords: Essential oil, ginger, quality index